Coughing up blood in tuberculosis: What three cases reveal about diagnosis and care - Ancila P; Pugazhendhi S; Maria Jose (Asian Journal of Medical Sciences)
Hemoptysis, or coughing blood, is a significant and potentially life-threatening symptom of pulmonary tuberculosis (PTB). The severity of hemoptysis can vary from mild to life-threatening, with massive hemoptysis posing severe risks due to hemodynamic instability and airway compromise. The diagnostic process is complicated by the multiple etiologies of hemoptysis in post-PTB patients, necessitating the use of comprehensive imaging techniques such as computed tomography angiography. Treatment options include arterial embolization, which is preferred over surgical intervention because of the poor respiratory reserve observed in most PTB cases. This case series highlights three distinct presentations of hemoptysis in patients with PTB, including Rasmussen’s aneurysm, tuberculosis-associated malignancy, and PTB in a genetically predisposed individual, illustrating the spectrum of complications, including Rasmussen’s aneurysm, malignancy, and active infection in a genetically predisposed patient. This report emphasises the importance of a comprehensive diagnostic approach and individualised treatment strategies for optimal patient outcomes.